Industrial training report: SWOT and PESTEL analysis of Employees’ Provident Fund (EPF) / Nur Irdina Iwani Mohd Faizal - Mohd Faizal, Nur Irdina Iwani (Universiti Teknologi MARA, Perlis, 2024)
Industrial report is one of the compulsory subjects that need to be completed and taken for every student of Bachelor in Business Administration (Hons) Human Resource Management. Employees’ Provident Fund (EPF) is one of the companies that I chose to undergo my industrial training programme for being an internship student that allows me to apply the knowledge learned in the academic program. The duration is from 3 September 2023 until 8 February 2024. I have been assigned to the Enforcement Section but still need to do the work in different sections. This report aims to provide an overview of my internship experience and offer recommendations for organizational improvement to ensure more individuals contribute to the EPF. This report covers several parts, including my resume, the company’s background, reflections on training during the internship, a Pestle, SWOT analysis, and matrix. Furthermore, I can acquire skills at the workplace in the industry and gain practical experience that can be used for future careers.